A 1D Magnetoelectric Sensor Array for Magnetic Sketching. Issue 3 (5th December 2018) - Chu, Zhaoqiang; Shi, Weiliang; Shi, Huaduo; Chen, Qingxiao; Wang, Lei; PourhosseiniAsl, Mohammad Javad; Xiao, Chijie; Xie, Tianyu; Dong, Shuxiang
Abstract: Although various magnetic sensors have been developed, tiny magnetic object detection is still a challenging issue in some cases, such as capsule position detection, endoscope navigation, and the detection of magnetic devices hidden in/on the human body. In this paper, a magnetic detecting and sketching system utilizing a 1D magnetic sensor array with 56 magnetoelectric (ME) sensing units is proposed. The ME sensors used in this system are based on a (1‐1) connectivity Metglas/piezofiber composite operating in the longitudinally magnetized and transversely poled (L‐T) mode. Simulation and experiment results show that the proposed magnetic detecting system can not only monitor the 2D position of a running magnetic metal object, but it can also identify its posture and length‐diameter ratio. The proposed magnetic detecting method is, therefore, very promising for medical magnetic positioning and security checking. Abstract : A magnetic detection and sketching system utilizing a 1D magnetic sensor array with 56 magnetoelectric sensing units is proposed . Simulation and experimental results show that the proposed magnetic detecting system can not only find the 2D position of a running magnetic object, but it can also identify the posture and length‐diameter ratio of a magnetic bar.